Accidents to Ovarian Cysts - Jyoti, Mishru (Journal of Universal College of Medical Sciences, 2013)
DOI: http://dx.doi.org/10.3126/jucms.v1i2.8412 Journal of Universal College of Medical Sciences Vol.1(2) 2013: 46-53